Light Drop Resistor (LDR) as pH Sensor for Wastewater Treatment - Imam Saukani; Eko Nuraini (Department of Informatics Engineering, 2022)
The electroplating industry generates acidic or wet liquid wastes when operating. Improper waste treatment will cause severe problems for the environment. Under Article 1 Paragraph 7 of the 1997 Law of the Republic of Indonesia, environmental pollution is the entry/inclusion of living things, substances, energy, or other components into the environment or changes in the environmental order by human activities or natural processes. So that the quality of the environment decreases to a certain level, causing the environment becomes less or no longer function according to its designation. A light Drop Sensor (LDR) sensor is used to read the level of acidic or wet liquid waste. The resistance value of the LDR sensor will change directly proportional to the conditions of acidity or level of wetness, and this value will then be the basis for the following control processing. The data were collected by installing a series of LDR sensors with resistance and obtained the results as follows: the wastewater, which was very cloudy, dark, of the first and second filters, and clear, each of these conditions emitted voltages of 4.4 volts, 3.45 volts, 3.10 volts, 2.6 volts, and 0.2 volts.